The Human Neutrophil Subsets Defined by the Presence or Absence of OLFM4 Both Transmigrate into Tissue In Vivo and Give Rise to Distinct NETs In Vitro - Welin, Amanda (Public Library of Science, 2013)

(untitled)
Neutrophil heterogeneity was described decades ago, but it could not be elucidated at the time whether the existence of different neutrophil subsets had any biological relevance. It has been corroborated in recent years that neutrophil subsets, defined by differential expression of various markers, are indeed present in human blood, calling for renewed attention to this question. The expression of the granule protein olfactomedin 4 (OLFM4) has been suggested to define two such neutrophil subsets. We confirm the simultaneous presence of one OLFM4-positive and one OLFM4-negative neutrophil subpopulation as well as the localization of the protein to specific granules. In vitro, these neutrophil subsets displayed equal tendency to undergo apoptosis and phagocytose bacteria. In addition, the subpopulations were recruited equally to inflammatory sites in vivo, and this was true both in an experimental model of acute inflammation and in naturally occurring pathological joint inflammation. In line with its subcellular localization, only limited OLFM4 release was seen upon in vivo transmigration, and release through conventional degranulation required strong secretagogues. However, extracellular release of OLFM4 could be achieved upon formation of neutrophil extracellular traps (NETs) where it was detected only in a subset of the NETs. Although we were unable to demonstrate any functional differences between the OLFM4-defined subsets, our data show that different neutrophil subsets are present in inflamed tissue in vivo. Furthermore, we demonstrate NETs characterized by different markers for the first time, and our results open up for functions of OLFM4 itself in the extracellular space through exposure in NETs.